2013
DOI: 10.1128/aem.01673-13
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of Mercury by Methanobactin from Methylosinus trichosporium OB3b

Abstract: bMany methanotrophs have been shown to synthesize methanobactin, a novel biogenic copper-chelating agent or chalkophore. Methanobactin binds copper via two heterocyclic rings with associated enethiol groups. The structure of methanobactin suggests that it can bind other metals, including mercury. Here we report that methanobactin from Methylosinus trichosporium OB3b does indeed bind mercury when added as HgCl 2 and, in doing so, reduced toxicity associated with Hg(II) for both Alphaproteobacteria methanotrophs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…Interestingly, such a protective effect was seen in a variety of methanotrophs when exposed to mercury and mb-OB3b. These results suggest that mb secreted by any methanotroph could serve to protect the broader microbial community from mercury toxicity (184).…”
Section: Binding Of Other Metalsmentioning
confidence: 91%
See 4 more Smart Citations
“…Interestingly, such a protective effect was seen in a variety of methanotrophs when exposed to mercury and mb-OB3b. These results suggest that mb secreted by any methanotroph could serve to protect the broader microbial community from mercury toxicity (184).…”
Section: Binding Of Other Metalsmentioning
confidence: 91%
“…Specifically, by strongly binding mercury, mbs may significantly alter its speciation and bioavailability, thereby reducing its toxicity. Indeed, growth studies showed that in the presence of mercury, added as mercuric chloride, methanotrophic growth was completely inhibited, but growth did occur when mb was also added (184). Interestingly, such a protective effect was seen in a variety of methanotrophs when exposed to mercury and mb-OB3b.…”
Section: Binding Of Other Metalsmentioning
confidence: 95%
See 3 more Smart Citations